13x-3=5x-6

Simple and best practice solution for 13x-3=5x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13x-3=5x-6 equation:


Simplifying
13x + -3 = 5x + -6

Reorder the terms:
-3 + 13x = 5x + -6

Reorder the terms:
-3 + 13x = -6 + 5x

Solving
-3 + 13x = -6 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-3 + 13x + -5x = -6 + 5x + -5x

Combine like terms: 13x + -5x = 8x
-3 + 8x = -6 + 5x + -5x

Combine like terms: 5x + -5x = 0
-3 + 8x = -6 + 0
-3 + 8x = -6

Add '3' to each side of the equation.
-3 + 3 + 8x = -6 + 3

Combine like terms: -3 + 3 = 0
0 + 8x = -6 + 3
8x = -6 + 3

Combine like terms: -6 + 3 = -3
8x = -3

Divide each side by '8'.
x = -0.375

Simplifying
x = -0.375

See similar equations:

| 6(x-9)=-30 | | 4.33=495 | | 6+-7=8 | | 16x-3=7x+6 | | 4(36+9y)=-72 | | -7/83/4 | | 4r-6-3=4r-9 | | a(z+5)=32 | | 4x-13=3x-1 | | d−8/−2=12 | | 4(x+6)=3x+4 | | c+3=3(11-3c) | | 6.1=u-3.3 | | x+5y=4z | | 1/2(1/4) | | -9x-6=6x+9 | | 5/4t=10 | | -24=3/4j | | 2.5=g-7 | | (x+5)(x+5)-(x-3)(x+5)= | | 25/4*5/2 | | 15/a=-10 | | 3e+1=e+1 | | 2x+3=9x-1+x | | 2m+5=25+6m | | 7.2=y-6 | | 4x+17=4-7x | | 1/4h+9=-1/2h-11 | | 7.41=n-9.59 | | (3*62)-25+n=166 | | (2x+3)(3x+7)=0 | | 7x-13=2x-3 |

Equations solver categories